2021
DOI: 10.1155/2021/6677767
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Complementary and Alternative Medicine on Premature Ovarian Failure

Abstract: It has been confirmed by growing evidence that common hormone replacement therapy is associated with an increasing risk of causing cardiovascular disease and cancer, while complementary and alternative medicine (CAM) is gaining popularity and application in more and more patients with premature ovarian failure (POF). Although there is little data concerning the clinical safety and efficacy of CAM, the literature includes application studies on the phytoestrogen-rich herbal, acupuncture treatment and interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…For instance, TGF-β1 induces TEX14-IT1 transcription in a SMAD4-dependent manner, and TEX14-IT1 mediates the antiapoptotic and pro-proliferative effects of TGF-β1 in GCs [ 31 ]. SMAD4 is a key regulatory factor in the production of FSH [ 32 , 33 ]. Bone morphogenetic protein 15 (BMP15) regulates FSH receptor (FSHR) through TGF-β receptor II and SMAD4 signaling in porcine GCs to regulate follicular development [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, TGF-β1 induces TEX14-IT1 transcription in a SMAD4-dependent manner, and TEX14-IT1 mediates the antiapoptotic and pro-proliferative effects of TGF-β1 in GCs [ 31 ]. SMAD4 is a key regulatory factor in the production of FSH [ 32 , 33 ]. Bone morphogenetic protein 15 (BMP15) regulates FSH receptor (FSHR) through TGF-β receptor II and SMAD4 signaling in porcine GCs to regulate follicular development [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The problem can be further complicated by inaccurate quotations included in literature reviews; an example is the quotation of this protocol on auricular acupuncture for premature ovarian insufficiency [ 35 ]: “Luo et al (...) conducted a systematic review and meta-analysis of the efficacy and safety of ear acupuncture in the treatment of POI by searching multiple databases before August 2020. The results showed that stimulation of specific ear points can enhance the physiological functions of specific parts of the human body, promote qi and blood circulation, and regulate the reproductive function of the hypothalamus-pituitary-ovarian axis” [ 36 ]. This is particularly disturbing given the specific nature of the information derived from a protocol in which the authors state: “We expect to provide reference for premature ovarian insufficiency treatment in the field of traditional Chinese medicine”.…”
Section: Discussionmentioning
confidence: 99%
“…POF is characterized by premature depletion of ovarian follicles in approximately 3% of women younger than 40 years old which is diagnosed by high levels of gonadotropins such as luteinizing hormone (LH) and FSH, and low levels of gonadal hormones including estrogens and inhibins [27,28]. Interestingly, the administration of ICI to animal models of D-galactose-induced POF caused a significant reduction in LH and FSH levels, promotion of estrogen and anti-Müllerian hormone (AMH) production, and increased viability of granulosa cells, which were all assumed to be the result of strengthening the DNA repair system indicated by altered levels γH2AX and 53BP1 expression upon treatment with ICI [29].…”
Section: Icariin Modulates Reproductive Hormones Synthesismentioning
confidence: 99%